Soil organic matter content effects on dermal pesticide bioconcentration in American toads (Bufo americanus). (30th June 2016) - Van Meter, Robin J.; Glinski, Donna A.; Henderson, W. Matthew; Purucker, S.Thomas
Abstract: Pesticides have been implicated as a major factor in global amphibian declines and may pose great risk to terrestrial phase amphibians moving to and from breeding ponds on agricultural landscapes. Dermal uptake from soil is known to occur in amphibians, but predicting pesticide availability and bioconcentration across soil types is not well understood. The present study was designed to compare uptake of 5 current‐use pesticides (imidacloprid, atrazine, triadimefon, fipronil, and pendimethalin) in American toads ( Bufo americanus ) from exposure on soils with significant organic matter content differences (14.1% = high organic matter and 3.1% = low organic matter). We placed toads on high‐ or low‐organic matter soil after applying individual current‐use pesticides on the soil surface for an 8‐h exposure duration. Whole body tissue homogenates and soils were extracted and analyzed using liquid chromatography–mass spectrometry to determine pesticide tissue and soil concentration, as well as bioconcentration factor in toads. Tissue concentrations were greater on the low‐organic matter soil than the high‐organic matter soil across all pesticides (average ± standard error; 1.23 ± 0.35 ppm and 0.78 ± 0.23 ppm, respectively), and bioconcentration was significantly higher for toads on the low‐organic matter soil (analysis of covariance p = 0.002). Soil organic matter is known to play a significant role in the mobility of pesticides and bioavailability to living organisms. Agricultural soils typically have relatively lower organic matter content and serve as a functional habitat for amphibians. The potential for pesticide accumulation in amphibians moving throughout agricultural landscapes may be greater and should be considered in conservation and policy efforts. Environ Toxicol Chem 2016;35:2734–2741. © 2016 SETAC.